2023
DOI: 10.3390/plants12132552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light of Different Spectral Compositions on Pro/Antioxidant Status, Content of Some Pigments and Secondary Metabolites and Expression of Related Genes in Scots Pine

Abstract: The aim of this study was to investigate the effect of light quality (white fluorescent light, WFL, containing UV components), red light (RL, 660 nm), blue light (BL, 450 nm), and white LED light (WL, 450 + 580 nm) on the components of the cellular antioxidant system in Pinus sylvestris L. in needles, roots, and hypocotyls, focusing on the accumulation of key secondary metabolites and the expression of related genes. The qualitative and quantitative composition of carotenoids; the content of the main photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Light quality also affects the formation of secondary metabolites, including in conifers [42]. The activation of the biosynthesis of several secondary metabolites by light under different spectral compositions has been observed in higher plants [22]. Most often, this occurs because photoreceptors can bind to the promoter regions of the genes for light-dependent transcription factors, such as HY5 and PIFs, which, in turn, can change the expression of genes encoding key enzymes involved in the biosynthesis of phenylpropanoids, flavonoids and terpenoids [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light quality also affects the formation of secondary metabolites, including in conifers [42]. The activation of the biosynthesis of several secondary metabolites by light under different spectral compositions has been observed in higher plants [22]. Most often, this occurs because photoreceptors can bind to the promoter regions of the genes for light-dependent transcription factors, such as HY5 and PIFs, which, in turn, can change the expression of genes encoding key enzymes involved in the biosynthesis of phenylpropanoids, flavonoids and terpenoids [45].…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, we found that narrowband RL had a specific effect on Scots pine seedlings and plantlets [1,2,22]. We hypothesized that the RL activation of various PHY and auxin signaling components stimulates an increase in the number of xylem cells [2].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The combined response to light and heat is the subject of the study proposed by Krevlaski et al: using phytochrome mutants of the model angiosperm Arabidopsis thaliana, the authors offer evidence that a low red/far-red ratio is favourable for the prevention of PSII photoinhibition under moderate short-term thermal stress [11]. The stress-protective effect of red light is confirmed by Pashkovskiy et al, who report their experiment on the consequences of light quality manipulation on the secondary metabolism in Pinus sylvestris plantlets, observing effects on the quantity of antioxidants and carotenoids in needles [12].…”
mentioning
confidence: 92%